THE MEANING AND APPLICATION OF INDEPENDENT LEARNING IN THE PERSPECTIVE OF ISLAMIC EDUCATION - Mujib, Abdul; Taher, Zahdi (Ri'ayah: Jurnal Sosial dan Keagamaan, 2021)
A very interesting issue was discussed when the term "Freedom of Learning" was raised by the Minister of Education and Culture, Nadiem Makarim. All academics also gave comments, some were cynical and many gave praise. This reminds us that the activities in education and learning continue to be sought after and studied. Thetarget ideal is to bring future generations to excellence among other countries. However, any conception that is put forward needs to be tested academically on the basis of his thinking. That's not to say, every thought is immediately applied. In fact, once it is applied, it must be evaluated. In order not to get caught up in anomalies and even misconceptions on a national education scale. Speaking of national-scale education, of course referring to what is stated in the National Education System Law (UU Sisdiknas) Number 20 of 2003 "the development of the potential of students to become human beings who believe and fear God Almighty, have noble character, are healthy, knowledgeable, capable, creative, independent and become a democratic and responsible citizen.